Bioethics and support to women victims of sexual violence: literature review - Peixoto, Paula; de Santana Silva, Juciara; Lago da Silva Sena, Edite; Silva de Oliveira Boery, Rita Narriman; Yarid, Sérgio Donha (Acta Bioethica, 2016)
Review article whose purpose is to reflect the light of bioethics risk and protection, the results of a literature review on the care of women victims of sexual violence. Proceeded to search for journals indexed in the database of the Virtual Health Library and Scopus considering publications since 2003. Data collection was conducted in May 2013 using the keywords: “sexual violence”, “assistance”, “services to women’s health”, “abortion”, “pregnancy”. We retrieved 15 publications. The results were grouped into two thematic categories: bioethical issues related to women’s access to care services, and bioethical aspects present in attendance. The discussion took place in the light of bioethics risk and protection. The State must ensure universalide access to the victims of sexual violence and health professionals should be prepared for this bioethically care.